2018
DOI: 10.14295/oh.v24i3.1221
|View full text |Cite
|
Sign up to set email alerts
|

Brown seaweed extract enhances rooting and roots growth on Passiflora actinia Hook stem cuttings

Abstract: Passiflora actinia Hook (common name: ‘maracujá do mato’) is an important medicinal species due to significant sedative and anxiolytic activities. In order to commercially exploit the plant, however, studies on propagation to improve rooting in stem cuttings are needed. The present study was designed to evaluate the effect of the brown seaweed (Ascophyllum nodosum (L.) Le Jol.) extract when applied on P. actinia stem cuttings bases. Five concentrations of the extract in distilled water were evaluated: 0% (pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
2
13
0
1
Order By: Relevance
“…Thus, the application of seed extract enhances marigold physiological performance, increasing seed germination and seedling development. However, the use of algae extract had no effect on root morphology of Passiflora actinia [27] and ornamental sunflower seedlings [4]. A. nodosum extract promotes root development and, consequently, serves to effectively establish the seedling [23].…”
Section: Resultsmentioning
confidence: 92%
“…Thus, the application of seed extract enhances marigold physiological performance, increasing seed germination and seedling development. However, the use of algae extract had no effect on root morphology of Passiflora actinia [27] and ornamental sunflower seedlings [4]. A. nodosum extract promotes root development and, consequently, serves to effectively establish the seedling [23].…”
Section: Resultsmentioning
confidence: 92%
“…Seaweed extracts obtained from Ascophyllum nodosum (L.) Le Jolis applied to Passiflora actinia Hook. increased 10% of rooting with 40% seaweed extract [120]. The rooting stimulation of a commercial biostimulant-based seaweed extracts has been also demonstrated in woody cuttings of Camellia japonica L. [121].…”
Section: Use Of Plant Growth Regulators and Biostimulants For Increasing Root Biomassmentioning
confidence: 77%
“…(Ferrante et al, 2013) also observed that Actiwave® (Valagro Spa), a biostimulant, had a stimulating effect on the rooting of Camellia japonica cuttings. In a study conducted by (Nicola et al, 2006) on Mentha×Piperita, the use of natural rooting hormones for organic farming and environmental protection was recommended although the effects of natural rooting hormones and synthetic auxin group hormones on rooting of cuttings were found to be at the same level (Gomes et al, 2018) investigated the effect of brown seaweed on the rooting of Passiflora cuttings. 40% concentration of the organic-based preparation of brown seaweed increased the rooting rate by 10%.…”
Section: Resultsmentioning
confidence: 99%